THE IMPACT OF SOCIAL MEDIA USAGE ON MANNERS AND ETHICS AMONG ELEMENTARY SCHOOL STUDENTS - Rahmat Kurniawan; Sabrina Fitria Anwar; Aura Fajra; Abdu Rohman Zay Damanik (Journal of International Islamic Law, Human Right and Public Policy, 2025)
The rapid development of digital technology has significantly influenced social life, including among elementary school students. One of the most prominent phenomena is the increasing use of social media among children. This study aims to examine the influence of social media usage on the manners and ethics of elementary school students, both positively and negatively. The research method used is a literature review, conducted by analyzing relevant studies, articles, and books. The findings reveal that social media can serve as a learning tool, broaden knowledge, and enhance students’ creativity when accompanied by proper guidance from parents and teachers. However, excessive and uncontrolled use may lead to negative impacts, such as reduced empathy, the use of inappropriate language, and weakened face-to-face interactions. Therefore, the active roles of families, schools, and communities are essential in providing supervision and digital literacy education from an early age, so that social media can be utilized positively in shaping well-mannered and ethical behavior in students.